2015
DOI: 10.1007/s00464-015-4250-6
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and correlations of immediate, early delayed, and late delayed bleeding associated with endoscopic resection for gastric neoplasms

Abstract: IB significantly increases the risk of EDB and LDB, but EDB does not increase the risk of LDB. Histologically confirmed carcinoma or a prolonged time for resection increases the risk of post-ER IB. We recommend careful follow-up approaches following ER of a gastric mucosal lesion in high-risk patients to prevent a potentially critical occurrence of delayed bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Aspirin was used by 591 (24.7%) CCA cases and 2,129 (44.6%) controls. Aspirin use was significantly associated with a 2.7- to 3.6-fold decreased risk for all CCA subtypes [65]. Preclinical studies have already revealed that COX-2 is implicated in cholangiocarcinogenesis in vitro and in tumour growth in rats [66,67].…”
Section: Aspirinmentioning
confidence: 99%
“…Aspirin was used by 591 (24.7%) CCA cases and 2,129 (44.6%) controls. Aspirin use was significantly associated with a 2.7- to 3.6-fold decreased risk for all CCA subtypes [65]. Preclinical studies have already revealed that COX-2 is implicated in cholangiocarcinogenesis in vitro and in tumour growth in rats [66,67].…”
Section: Aspirinmentioning
confidence: 99%
“…The reported incidence of ESD-related bleeding varies. The reported intra-procedural and PEB rates were 11.9–45.1% and 5.1%, respectively 3,14,15 . Bleeding is inevitable during mucosal incision and submucosal dissection using an electrosurgical knife.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison, patients taking anticoagulation drugs have an increased risk of delayed bleeding of 6.7 % after esophageal endoscopic resection [32]. For gastric resection, about 10 % of resections are complicated by delayed bleeding, and this rate is similar in non-cirrhosis [33] and cirrhosis [34] cases. Duodenal resections are known to be prone to bleeding in non-cirrhosis populations, with an estimated rate of about 16 % [27,35,36].…”
Section: Discussionmentioning
confidence: 99%